TUNTUTAN KERJA (JOB DEMANDS) DAN KETERLIBATAN KERJA (JOB INVOLVEMENT) TERHADAP KETERIKATAN KERJA (WORK ENGAGEMENT) - Sinta Azkiah; Novita Dian Iva (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
This study aims to determine the effect of job demands and job involvement on work engagement. This study will use quantitative methods with a correlation research design.the subjects in this study were machining employees of PT. Padma Soode Indonesia, totaling 84 employees. This study uses a job demands scale with a Cronbach alpha reliability value of 0,931, a job involvement scale eith a Cronbach alpha reliability value of 0,883, and a work engagement scale with a Cronbach alpha reliability value of 0,900. The data analysis technique used Rank- Spearman correlation. This study found that there is an influence between job demands and job involvement on work engagement. There is a positive influence between job demands and work engagement based on the correlation test, so that job demands are a trigger to increase a sense of engagement at work. However, there is a positive relationship between work engagement and job involvement in the work environment can be categorized as social capital such as support from colleague, the suitability of values adopted by the company’s values makes employees more attached.